Qualitative detection of chromone from Centella asiatica (L.) - Vaidya A.L.3, Waghmare A.A.1, Narwade V.T. 2 and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Thin layer chromatography and spectroscopic methods were adopted for qualitative detection of choromone. Chromone from Centella asiatica was extracted by using different solvent and they are detected by paper chromatography.